2004
DOI: 10.3201/eid1005.030016
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium africanumCases, California

Abstract: Five Mycobacterium tuberculosis complex isolates in California were identified as M. africanum by spoligotyping, single nucleotide polymorphisms, a deletion mutation, and phenotypic traits, confirming it as a cause of tuberculosis in the United States. Three of the five patients from whom M. africanum was isolated had lived in Africa.M ycobacterium africanum is a member of the M. tuberculosis complex, which has been isolated from humans in equatorial Africa. The disease produced by M. africanum is similar to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…To further characterize the assay, we analyzed an additional 15 clinical isolates representing 15 distinct spoligotypes commonly associated with strains of M. bovis, as well as 5 clinical isolates of M. africanum (14). Whereas all 5 of the M. africanum isolates had the expected RD pattern, surprisingly, we found that our assay identified 13% (2/15) of these putative M. bovis isolates as MTC members other than classical M. bovis.…”
Section: Resultsmentioning
confidence: 90%
“…To further characterize the assay, we analyzed an additional 15 clinical isolates representing 15 distinct spoligotypes commonly associated with strains of M. bovis, as well as 5 clinical isolates of M. africanum (14). Whereas all 5 of the M. africanum isolates had the expected RD pattern, surprisingly, we found that our assay identified 13% (2/15) of these putative M. bovis isolates as MTC members other than classical M. bovis.…”
Section: Resultsmentioning
confidence: 90%
“…Today, M. africanum is rarely isolated outside of West Africa, typically in first degree immigrants [62]. In a study in Ghana, host polymorphisms were identified with differential protection against M. tuberculosis versus M. africanum in both directions [63], [64], although the degree of selective advantage conferred by these polymorphisms is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…DNA from both M. africanum and M. tuberculosis sensu stricto was recovered from Egyptian mummies (28), yet today M. africanum isolates are rarely encountered outside of West Africa, except among first-generation immigrants (8). This lack of spread of M. africanum, despite large migrations, such as through the slave trade to the New World, (6).…”
Section: Discussionmentioning
confidence: 99%